2012
DOI: 10.1007/s10295-011-1060-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from alkali-treated rice straw via simultaneous saccharification and fermentation using newly isolated thermotolerant Pichia kudriavzevii HOP-1

Abstract: In this study, simultaneous saccharification and fermentation (SSF) was employed to produce ethanol from 1% sodium hydroxide-treated rice straw in a thermostatically controlled glass reactor using 20 FPU gds⁻¹ cellulase, 50 IU gds⁻¹ β-glucosidase, 15 IU gds⁻¹ pectinase and a newly isolated thermotolerant Pichia kudriavzevii HOP-1 strain. Scanning electron micrograph images showed that the size of the P. kudriavzevii cells ranged from 2.48 to 6.93 μm in diameter while the shape of the cells varied from oval, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 35 publications
6
75
0
4
Order By: Relevance
“…In this study, both M. guilliermondii and S. cerevisiae exhibited a low degree of flexibility towards the conversion of galactose to ethanol (figure 4B). The weak assimilation of galactose tallies with reports that suggest most yeast species are not fully adaptable towards galactose metabolism [21], [38]. This observation could be attributed to several factors including but not limited to its proton transport assembly and slow substrate affinities of its metabolic enzymes which could eventually cause feedback inhibition, thus decreasing the output.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study, both M. guilliermondii and S. cerevisiae exhibited a low degree of flexibility towards the conversion of galactose to ethanol (figure 4B). The weak assimilation of galactose tallies with reports that suggest most yeast species are not fully adaptable towards galactose metabolism [21], [38]. This observation could be attributed to several factors including but not limited to its proton transport assembly and slow substrate affinities of its metabolic enzymes which could eventually cause feedback inhibition, thus decreasing the output.…”
Section: Discussionsupporting
confidence: 64%
“…Some of these unique non Saccharomyces yeasts include Zygosaccharomyces rouxii [14], [16], [17], [18]. Kluyveromyces marxianus [19], [20], Pichia kudriavzevii [21], [22], Dekkera bruxellensis [23], Zygosaccharomyces bailii [24]. Meyerozyma guilliermondii, a telemorph of Candida guilliermondii or wine yeast is one of such promising non Saccharomyces yeasts obtained from environmental samples with unique biotechnological applications and biological control potential [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…This type of yeast was isolated from various sources, such as cotton stalks and straw (containing lignocellulosic hydrolyzates), subjected to different treatments, including enzymatic hydrolysis with cellulases. This strain showed better ethanol production (up to 200%) under conditions of high temperature, compared to S. cerevisiae (Dhaliwal et al, 2011;Isono et al, 2011;Kaur et al, 2011;Oberoi et al, 2012). Fonseca (2009) have reported to use of a strain of I. orientalis to reduce the toxic components of hemicellulosic hydrolyzates.…”
Section: Discussionmentioning
confidence: 97%
“…D. bruxellensis and S. cerevisiae possesses an almost similar molecular mechanism for this trait (Piskur et al, 2006). Kwon et al (2011) reported that P. kudriavzevii is extremely tolerant to 3 g/L furfural and also tolerate acetic acid of up to 10 g/L (Oberoi et al, 2012) and formic acid up to 2 g/L (Dandi et al, 2013). The genetic engineering tools for this yeast are limited, and genome sequence has recently been reported by Chan et al (2012).…”
Section: Improvement Of Tolerance Against Inhibitors and Biofuel Prodmentioning
confidence: 99%